EVALUASI PEMBELAJARAN PENDIDIKAN AGAMA ISLAM DI SMA NEGERI 3 SURAKARTA JAWA TENGAH The Evaluation of the Islamic Education at SMA 3 Surakarta Central Java - Yustiani Yustiani (Balai Penelitian dan Pengembangan Agama Semarang, 2017)
Evaluation on curriculum has been conducted periodically and continuously in order to understand the implementation of curriculum based on the basis, function, and the goal of national education, and its suitability with the community development. This research is a part of evaluation process on the education which is suitable with curriculum 2013. This study focuses on the subject of Islamic teaching in State Senior High School 3 Surakarta. This is an evaluative research using an evaluation model called CIPP (Context, Input, Process, and Product) and a descriptive qualitative approach. Result of this study shows: (1) context evaluation shows that PAI teaching has applied scientific approach seen in RPP and practice of education process, (2) Input aspect is good as seen in the availability of standard documents either in school, PAI teacher, the availability of infrastructures, and the policy of head master. (3) Process evaluation is in accord with the standard process of curriculum 2013 in RPP elements. (4) Product aspect is seen in the implementation of authentic appraisal including behavior, attitude, knowledge and skills assessment.